Naturally Derived Heme-Oxygenase 1 Inducers and Their Therapeutic Application to Immune-Mediated Diseases - Funes, Samanta C.; Rios, Mariana; Fernández-Fierro, Ayleen; Covián, Camila; Bueno, Susan M.; Riedel, Claudia A.; Mackern-Oberti, Juan Pablo; Kalergis, Alexis M. (Frontiers in Immunology, 2020)
Heme-oxygenase (HO) is the primary antioxidant enzyme involved in heme group degradation. A variety of stimuli triggers the expression of the inducible HO-1 isoform, which is modulated by its substrate and cellular stressors. A major anti-inflammatory role has been assigned to the HO-1 activity. Therefore, in recent years HO-1 induction has been employed as an approach to treating several disorders displaying some immune alterations components, such as exacerbated inflammation or self-reactivity. Many natural compounds have shown to be effective inductors of HO-1 without cytotoxic effects; among them, most are chemicals present in plants used as food, flavoring, and medicine. Here we discuss some naturally derived compounds involved in HO-1 induction, their impact in the immune response modulation, and the beneficial effect in diverse autoimmune disorders. We conclude that the use of some compounds from natural sources able to induce HO-1 is an attractive lifestyle towards promoting human health. This review opens a new outlook on the investigation of naturally derived HO-1 inducers, mainly concerning to autoimmunity.